2013
DOI: 10.1021/nn4000644
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Insight into the Origin of Red and Blue Photoluminescence Arising from Freestanding Silicon Nanocrystals

Abstract: Silicon nanocrystals (Si NCs) are attractive functional materials. They are compatible with standard electronics and communications platforms as well being biocompatible. Numerous methods have been developed to realize size-controlled Si NC synthesis. While these procedures produce Si NCs that appear identical, their optical responses can differ dramatically. Si NCs prepared using high-temperature methods routinely exhibit photoluminescence agreeing with the effective mass approximation (EMA), while those prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
356
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(391 citation statements)
references
References 52 publications
31
356
0
4
Order By: Relevance
“…There is increasing evidence to suggest that the blue emission is governed by electron transfer from the surface states [96,121]. Remarkably, recent observations suggest that certain electron donating, nitrogen containing species can drastically improve the blue emitting quantum yield of silicon quantum dots significantly.…”
Section: Preparation and The Impacts Of Surface Chemistrymentioning
confidence: 99%
“…There is increasing evidence to suggest that the blue emission is governed by electron transfer from the surface states [96,121]. Remarkably, recent observations suggest that certain electron donating, nitrogen containing species can drastically improve the blue emitting quantum yield of silicon quantum dots significantly.…”
Section: Preparation and The Impacts Of Surface Chemistrymentioning
confidence: 99%
“…[14][15][16][17] The size tunable emission [18][19][20] , high brightness 21 , and high photostability compared to organic dyes 22 , have made SiNPs attractive materials as fluorescent cellular markers. In addition, silicon is abundant and economical 23 but more importantly silicon has low inherent toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure 2.1, the IR spectrum of the dried polymer contains overlapping peaks at 1050 cm -1 and 1090 cm -1 , both of which are in the region that has been attributed to Si-O bonding. 9,34,40,47,58,63,69,72,[75][76][77][78][79][80][81][82][83] Evidence for the preservation of Si-H bonding is also shown by the peak at 2240 cm -1 in the IR spectrum.…”
Section: Synthesis Of Polymeric Hsio 15 From Hsiclmentioning
confidence: 93%
“…61 Conversely, others have reported the development of high energy PL from originally red-emitting Si NPs concurrent with surface oxidation. 63,67 For example, in a study conducted by our group, we characterized changes in the photophysical properties of initially 690 nm-emitting (d = 4 nm, λ exc = 370 nm), alkylpassivated Si NPs following exposure to a series of n-alcohols varying in hydrocarbon chain length. 67 We reported that the development of surface oxide (observed by FT-IR)…”
Section: Effect Of Defects On Photoluminescence From Silicon Nanopartmentioning
confidence: 99%
See 1 more Smart Citation